Survey of Some Fungal Diseases on Leaves of Rose Plants in Al-Bayda City, Libya - Mohamed, Nwara A; Abdullah , Nawal G.; El-Sanousi, Omar M. (Al-Mukhtar Journal of Sciences, 2019)
This study was conducted on rose plants growing in El-Beida City's in 2016 to survey the fungal diseases on leaves of this plant. The results of this study indicated that the infection on roses planted in public gardens (parks) was more significant than that of home or nursery planted roses, and these results showed that the amount of disease on leaves of roses grown in El-Beida were high during the period of this study, Home gardens and nurseries were the least infected (45.5% and 48.3%) respectively, compared to parks (73%). The reported diseases in this study were powdery mildew, rust, black spot, silver spot, burning margins and blotches, the most disease occurring was powdery mildew disease at (46.9% and 30.4%) for both incidence rate and severity respectively on cultivated roses in El-Bieda City, While rust was the least registered disease during the year 2016 with an infection rate that did not exceed an average of 4.1%. There are no significant differences between the trends and incidences of infection range between 37.5-40%. July was the highest month in terms of infection and the older leaves of roses had the highest infection rate through all the months of our study.